Mechanically activated alite: New insights into alite hydration - Bergold, Sebastian; Neubauer, Jürgen; Götz-Neunhoeffer, Friedlinde (Cement and Concrete Research, 2015)
For superior understanding of alite hydration an investigation of mechanically activated alite (M3 modification) was performed by XRD and heat flow calorimetry. Activation resulted in reduced particle size, a decreased mean crystallite size and partial amorphization. For the samples of activated alite a significantly accelerated and intensified hydration was observed and complete conversion of alite was found after 24 h. The enthalpy of reaction for crystalline alite was determined to be - 548 J/g from measured heat of hydration after 24 h. The enthalpy of reaction of amorphous "alite" was found to be less exothermic (- 386 J/g). The main hydration period is controlled by nucleation of C-S-H, while the transition from acceleration to deceleration period takes place after consumption of the small alite particles. XRD amorphous C-S-H phase is indicated to precipitate in considerable amount even in the highest activated alite before "long-range ordered", XRD detectable C-S-H was observed.
Keywords: Acceleration (A); Amorphous material (B); Ca3SiO5 (D); Calcium-Silicate-Hydrate (C-S-H) (B); Hydration (A)